PENGARUH LIKUIDITAS, LEVERAGE, KOMISARIS INDEPENDEN DAN UKURAN PERUSAHAAN TERHADAP AGRESIVITAS PAJAK PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2012-2015 - Indah Yulitasari, 12.05.52.0019; Maryono, Maryono (Students Journal of Accounting and Banking, 2016)
This study aimed to analyze the effect of firm likuidity, leverage, independent commissioner and size to agrressiveness taxes. The object of this study is Manufacturing Company listed on the Indonesia Stock Exchange (IDX) 2012-2015. The sampling method used is purpose sampling the study period of 2012 throught 2015. The data analysis technique used is multiple linear regression.Â  The results of this study indicate that the hypothesis testing showed that the variable leverage had positive effect and significant to the Agressiveness Taxes. Independent commissioner and Size had positive and no significant. Where as liquidity has negative effect and no significant on Aggressiveness Taxes. Â Keywords: Firm Liquidity, Leverage, Independent Commissioner, Size and Aggressiveness Taxes